Open modernisms - Ross, Stephen, 1970-; Huculak, J. Matthew; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2016)
"Open Modernisms is an open, Creative-Commons-licensed online platform that allows teachers and scholars to build custom anthologies of out-of-copyright primary materials for the period 1850-1950. It uses a custom-built Islandora module to host a library of documents from which users can select and rearrange in whatever order they like; add their own notes and introductory or contextualizing materials; and output in a numbered sequence of files for digital distribution and/or printing. The site and its materials are open access, and the code for the site, based on already-existing open-source software, is hosted on Github for easy repurposing and distribution. The code can be adapted for any discipline. Create. Mix. Share."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Project Leads: Dr. J. Matthew Huculak, Dr. Stephen Ross.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on March 31, 2016).
Keywords: English literature; Electronic books